Problematic issues of diagnosis of trophoblastic disease - Н. Ю. Педаченко; О. І. Мухомор; К. Л. Аветисьян; Ю. С. Денисенко (Publishing House TRILIST, 2017)
The article investigates the difficulties of diagnosis of trophoblastic disease in practice. Till nowadays there is no general strategy in the detection and treatment of gestational trophoblastic disease, as there is no clear status. The diagnosis of this pathology is multifactorial in nature, which also presents some difficulties in the timely detection of gestational trophoblastic disease. This shown that the occurrence of this disease depends on many factors, including the important role of pathogenetic predisposition. In the current study the features of diferrential diagnosis of trophoblastic disease in the early stages of development by ultrasonography and hystologycal analysis were investigated. It was proved that these studies play an important role in the differentiation of uterine molar pregnancy. A clinical case is presented, in which disagreements in diagnoses of a pregnant patient are noted. Also there is a need to respect modern principles of medical ethics and deontology (another device, "other eye" of researcher). As the authors of the article notes, the interpretation of cases with pathology of small pregnancy terms should implemented by doctors of diagnosts together with gynecologists, who have sufficient experience and special training on the problems of trophoblastic disease. In this case, the ultrasound data in the dynamics and the results of clinical and laboratory studies should be taken into account in the complex. Histological studies should be carried out by doctors in specialized institutions (oncological centers, scientific institutions of the 4th level). This problem continues to be relevant, given the high risk of transformation of the physiological conditions of pregnancy into oncopathology, and radical decisions in such cases should be taken by the consilium. With the increase in the number of pregnant women after infertility treatment, including methods of assisted reproduction, such cases can happen more often for different reasons. Therefore doctors who are entrusted to watch and treat such patients should always take into account the significant moral, psychological and possibly additional legal aspects, the occurrence of which can often be foreseen and prevented.